Atari : between a rock and a hard place - Shein, James B., 1942-; Crown, Judith ([London] : SAGE, 2016)
Atari, a maker of video games, went through several owners over the years, winding up controlled by Infogrames, a French publisher of video games. Infogrames later sold Atari shares in a secondary public offering, eventually reducing the parent's share to 51.6 percent by September 2005 and creating a complicated two-tier ownership structure. This study examines the multiple challenges which were faced by Atari's management.
Originally Published in: Shein, J., & Crown, J. (2011). Atari: Between a rock and a hard place. 5-210-260. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Atari, Inc; Consolidation and merger of corporations -- Case studies; Corporate governance -- Case studies